NATURAL SCHOOL MANAGEMENT: A NEW CONCEPT OF EDUCATION - Firman Firman (Dinasti International Journal of Education Management And Social Science, 2020)
Natural school is one of the new concepts in the world of education. A natural school is basically an alternative form of education that uses the universe as a place of learning, teaching material, and as an object of learning. According to some experts, it is believed that this concept is an effective approach for the realization of activities related to active learning. The aims of this research are to investigate how the management of natural schools works, specifically in planning, organizing, actuating, and controlling. This study used a qualitative method with a case study approach. The data were collected through semi-structured interviews, observation, and documentation. The data were then analyzed, described, and interpreted comprehensively. The data revealed that character education and religion are emphasized to the students in the teaching and learning process.